2022
DOI: 10.1101/2022.02.14.480431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel ERR pan-agonists ameliorate heart failure through boosting cardiac fatty acid metabolism and mitochondrial function

Abstract: Cardiac metabolic dysfunction is a hallmark of heart failure. Estrogen related receptors ERRα and ERRγ are essential regulators for cardiac metabolism. Therefore, activation of ERR could be a potential therapeutic intervention for heart failure. However, no natural or synthetic ERR agonist is available to demonstrate their pharmacological effect in vivo. Using a structure-based design approach, we designed and synthesized two structurally distinct pan-ERR agonists, SLU-PP-332 (332) and SLU-PP-915 (915), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Interestingly, these pathways are quite distinct from those identified as downregulated in the skeletal muscle ERRα/γ double KO mice, where oxidative phosphorylation, TCA cycle, and mitochondrial function genes were well represented. 37 However, we previously showed that SLU-PP-332 induced a similar set of energetic genes/pathways in cardiomyocytes 38 as were downregulated in the skeletal muscle double ERRα/γ KO consistent with SLU-PP-332 activation of ERRs. Thus, the pathways regulated by SLU-PP-332 may be distinct for the skeletal muscle.…”
Section: ■ Results and Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Interestingly, these pathways are quite distinct from those identified as downregulated in the skeletal muscle ERRα/γ double KO mice, where oxidative phosphorylation, TCA cycle, and mitochondrial function genes were well represented. 37 However, we previously showed that SLU-PP-332 induced a similar set of energetic genes/pathways in cardiomyocytes 38 as were downregulated in the skeletal muscle double ERRα/γ KO consistent with SLU-PP-332 activation of ERRs. Thus, the pathways regulated by SLU-PP-332 may be distinct for the skeletal muscle.…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…Thus, the pathways regulated by SLU-PP-332 may be distinct for the skeletal muscle. Importantly, SLU-PP-332 was very effective in improving heart function in a model of heart failure that was coupled to its ability to enhance fatty acid oxidation and mitochondrial metabolism, 38 validating its function as an ERR agonist. In the cardiomyocytes, the effect of SLU-PP-332 had effects on gene expression that was mediated by each of the ERRs (ERRα, β, and γ), whereas the effects that we observed on enhanced exercise capacity appeared to be mediated primarily through ERRα.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…We previously observed that the ERR agonist SLU-PP-915 increases transcription of autophagy related genes and increases autophagic flux. 23 Based on our analysis of the autophagic genes induced by activation of ERR, we hypothesized that TFEB induced by pharmacological activation of the ERRs may be the key factor underlying induction of the pathway. Here, utilizing both primary cardiomyocytes (NRVMs) and mouse myoblasts (C 2 C 12 ) we demonstrated: 1) Agonizing ERR with SLU-PP-915 increases gene and protein expression of TFEB, to a physiological level of autophagy induction as compared with starvation; 2) ERR binds to the Tfeb promoter and the Tfeb promoter confers ERR responsiveness to a luciferase reporter gene; 3) when the region containing 2 putative ERREs is deleted from the Tfeb promoter, the ERR responsiveness of the reporter is eliminated; 4) after treatment of ERR agonist, TFEB target genes are induced, suggesting a signaling cascade event.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 We recently described two novel high affinity ERR agonists (SLU-PP-332 and SLU-PP-915) that have sufficient pharmacokinetic properties to use in animal models of disease. 22,23 Recently, we found that treatment of mice with heart failure with these ERR agonists improved cardiac function and noted a substantial increase in expression of genes in the autophagy pathway. 23 Furthermore, we observed that SLU-PP-915 increases autophagic flux in neonatal rat ventricular myocytes (NRVMs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation